FENOMENA PEMBUBARAN DAN PENOLAKAN PENGAJIAN PERSPEKTIF FIKIH DAN HUKUM POSITIF DI INDONESIA - Guntur Prawito (PROGRAM STUDI ILMU KOMUNIKASI, 2023)
ABSTRACT In Indonesia, Islam is represented by numerous organizational backgrounds and understandings, such as Nahdatul Ulama (NU), Muhammadiyah, Persis (Islamic Association), Salafi, Al-Irsyad, LDII (Indonesian Islamic Da'wah Institute), and others. Not infrequently, the execution of the recitation by one of the groups rejects, persecutes, or forcibly disbands the study by those who have different interpretations of amar ma'ruf nahi mungkar. Variances in fiqh between organizations and groups are due to postulate technique variances. This research employs a normative juridical, library law research method that involves the analysis of library items and secondary data. The goal of this study is to educate and advise Muslims in Indonesia on how to deal with fiqh disagreements. According to the findings of this study, the act of disbanding and refusing to recite the recitation is suspected of attacking fiqh related to morals to fellow Muslims, because it includes acts of attacking suspicion, igniting it, breaking ukhuwah, and refusing to stay in touch or seek explanations from one another. The importance of communication between Islamic groups and organizations in overcoming this problem cannot be overstated. In terms of positive law in Indonesia, it is suspected of violating Article 28 Letter E paragraphs 1 and 3 of the 1945 NKRI Constitution, Article 28 paragraph 2 of Law Number 11 of 2008, and Article 1365 of the Civil Code addressing unlawful acts. Keywords: Fiqh, Positive Law, Tabayun